Polyvinylamine gas separation membrane as well as preparation method and application thereof

By introducing silver nanowires with surface-loaded MOFs into the polyvinylamine gas separation membrane, the problem of reducing separation efficiency caused by excessive primary amino content is solved, and the effect of improving the CO2 permeability rate and separation coefficient is achieved.

CN119680407AActive Publication Date: 2025-03-25HUANENG CLEAN ENERGY RES INST +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510094874.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-03-25
Estimated Expiration
2045-01-21

AI Technical Summary

Technical Problem

In the existing polyvinylamine (PVAm) gas separation membrane, excessive primary amino content leads to regular arrangement of polymer chains and crystallization regions, thereby reducing separation efficiency.

Method used

The polyvinylamine gas separation membrane introduces silver nanowires with surface-loaded MOFs. The silver nanowires can regulate the arrangement of polyvinylamine segments to avoid the formation of crystallization zones. At the same time, MOFs provide additional CO2 adsorption sites to improve separation performance.

Benefits of technology

By introducing silver nanowires loaded with MOFs on the surface, the permeability rate and separation coefficient of CO2 are improved, and primary amino groups are avoided to form crystallization regions through NH2-NH2 interaction, which enhances the separation performance of the gas separation membrane.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119680407A_ABST
    Figure CN119680407A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of gas separation, and particularly relates to a polyvinylamine gas separation membrane as well as a preparation method and application thereof. The polyvinylamine gas separation membrane provided by the invention comprises polyvinylamine and silver nanowires of which the surfaces are loaded with MOFs (Metal-Organic Frameworks). Silver nanowires loaded with MOFs on the surfaces are introduced into the gas separation membrane, the silver nanowires can effectively regulate and control arrangement of polyvinylamine chain segments, formation of a crystalline region is avoided, the MOFs can provide additional CO2 adsorption sites, and the CO2 separation performance of the gas separation membrane is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of gas separation, and in particular relates to a polyethylene amine gas separation membrane and a preparation method and application thereof. Background Art

[0002] In recent years, the greenhouse effect has become one of the most concerned environmental issues. The main source of the greenhouse effect is CO2, which is mainly emitted by power plants, steel mills and chemical plants. From the perspective of preventing global warming, the development of efficient capture and recovery technology for carbon dioxide has become a top priority.

[0003] The main carbon dioxide capture technologies include absorption separation, adsorption separation, cryogenic distillation, chemical cycle combustion, membrane separation, hydrate, etc. Among them, membrane separation, as an emerging carbon dioxide capture technology, has the advantages of mild operating conditions, easy scale-up, environmental friendliness, and small footprint, and has become a hot spot in carbon dioxide capture technology.

[0004] Among the many facilitated transfer membrane materials, the permeation selectivity of polyvinylamine (PVAm) membrane is in a leading position and has the possibility of being the first to achieve large-scale industrial application. The group that can transfer carbon dioxide in PVAm membrane is primary amine group (-NH2), and the carbon dioxide separation performance mainly depends on the content of primary amine group and the efficiency of carbon dioxide transfer. Increasing the primary amine content in PVAm membrane is conducive to improving the permeation rate and separation coefficient of carbon dioxide, but too high a primary amine content will lead to regular arrangement of polymer chains and the formation of crystalline areas, which will lead to a decrease in separation efficiency.

[0005] Therefore, how to avoid the problems caused by excessive primary amino group content is an issue that needs to be solved urgently at this stage. Summary of the invention

[0006] The present invention is based on the inventor's discovery and understanding of the following facts and problems:

[0007] Liu Chengcen's research group at Taiyuan University of Technology introduced halloysite nanotubes (HNTs) into polyvinylamine (PVAm) to prepare PVAm-HNTs / PSf mixed matrix membrane. The CO2 permeation rate of the mixed matrix membrane can reach 178GPU, and the CO2 / N2 selectivity is 83. However, due to the complex preparation process and high cost of halloysite nanotubes, it is impossible to achieve industrial mass production.

[0008] The present invention aims to solve one of the technical problems in the related art to at least a certain extent. To this end, an embodiment of the present invention provides a polyethylene amine gas separation membrane, in which silver nanowires loaded with MOFs on the surface are introduced, the silver nanowires can effectively regulate the arrangement of polyethylene amine segments to avoid the formation of crystalline regions, and MOFs can provide additional CO2 adsorption sites, further improving the separation performance of the gas separation membrane for CO2.

[0009] The polyvinylamine gas separation membrane of the embodiment of the present invention comprises polyvinylamine and silver nanowires with MOFs loaded on the surface.

[0010] The advantages and technical effects brought by the polyethylene amine gas separation membrane of the embodiment of the present invention are as follows: 1. In the embodiment of the present invention, after MOFs are loaded on the surface of the silver nanowires, additional CO2 adsorption sites are provided, which is beneficial to improving the CO2 separation performance; 2. In the embodiment of the present invention, silver nanowires with MOFs loaded on the surface are introduced into the gas separation membrane, which can form intercalations between the primary amino groups of polyethylene amine, avoiding the primary amino groups from forming crystalline regions through NH2-NH2 interactions and losing the function of transferring carbon dioxide; 3. In the embodiment of the present invention, silver nanowires with MOFs loaded on the surface are introduced into the gas separation membrane, and the silver nanowires can provide adsorption sites for CO2, play a role in physical adsorption, transfer CO2 to the other side of the membrane, and increase the transfer rate of CO2. The MOFs loaded on the surface of the silver nanowires can provide additional adsorption sites, further improving the CO2 separation performance.

[0011] In some embodiments, the content of the silver nanowires loaded with MOFs on the surface in the polyethylene amine gas separation membrane is 20-85 wt %.

[0012] In some embodiments, the silver nanowires have a diameter of 3 to 18 μm and a length of 20 to 60 nm.

[0013] In some embodiments, the loading amount of MOFs on the surface of the silver nanowires is 10-30 wt %.

[0014] In some embodiments, the polyethyleneamine gas separation membrane has a thickness of 300 to 800 nm.

[0015] The present invention also provides a method for preparing an ethyleneamine gas separation membrane, comprising the following steps:

[0016] (1) adding an organic ligand to a silver nanowire solution and performing ultrasonic dispersion treatment to obtain a mixed solution of the organic ligand and the silver nanowires;

[0017] (2) adding a metal salt solution to the mixed solution obtained in step (1), heating the mixed solution, stirring the mixed solution, and then standing the mixed solution for aging, washing and drying the obtained product to obtain silver nanowires with MOFs on the surface, and using water as a solvent to obtain a silver nanowire solution with MOFs on the surface;

[0018] (3) adding the surface-loaded MOFs silver nanowire solution obtained in step (2) to the polyvinylamine solution, and then adding polyvinyl alcohol to obtain a slurry, and coating the slurry on an ultrafiltration membrane, followed by drying.

[0019] In some embodiments, in step (1), the organic ligand includes at least one of 2,3,6,7,10,11-hexaaminotriphenyl hexahydrochloride, 1,3,5-benzenetricarboxylic acid, 1,3,5-tris(4-carboxyphenyl)benzene, 1,4-cyclohexanedicarboxylic acid or 1,10-phenanthroline;

[0020] and / or, the mass ratio of the organic ligand to the silver nanowire is 1:(2-10);

[0021] And / or, the preparation method of the silver nanowires comprises: adding polyvinyl pyrrolidone to ethylene glycol, heating it for reaction and then cooling it, adding silver nitrate solution and ferric chloride solution, cooling it after the silver nanowires are formed, centrifuging it with acetone to obtain a precipitate, and preparing a silver nanowire solution with ethanol as a solvent;

[0022] Preferably, the dosage ratio of polyvinyl pyrrolidone to ethylene glycol is 4 to 20 g / L;

[0023] and / or, the concentration of the silver nitrate solution is 0.01-0.1 mol / L, the concentration of the ferric chloride solution is 0.1-1 mol / L, and the volume ratio of the ethylene glycol, the silver nitrate solution and the ferric chloride solution is (1-10):(1-5):1;

[0024] And / or, the reaction temperature is 140-180° C., and the reaction time is 0.5-2 h.

[0025] In some embodiments, in step (2), the metal salt solution includes at least one of zinc nitrate, cobalt nitrate or copper nitrate;

[0026] and / or, the molar ratio of the metal to the organic ligand in the metal salt solution is 1:(2-12);

[0027] And / or, the stirring treatment temperature is 30-80°C, the stirring treatment time is 1-4 hours, and the static aging time is 0.5-12 hours;

[0028] And / or, the concentration of the silver nanowire solution loaded with MOFs on the surface is 1-10 wt%

[0029] In some embodiments, in step (3), the silver nanowires loaded with MOFs on the surface account for 20 to 85% of the mass of the polyethylene amine gas separation membrane;

[0030] And / or, the mass ratio of the polyvinyl amine to the polyvinyl alcohol is 20:(1-10);

[0031] And / or, the slurry is coated on the ultrafiltration membrane to a thickness of 50 to 200 μm;

[0032] And / or, the preparation method of the polyvinylamine solution comprises: dissolving N-vinylformamide and 2,2-azobis(2-methylpropylimidamide) dihydrochloride in deionized water, heating under nitrogen protection, and performing free radical polymerization reaction to obtain a polyvinylformamide solution; then adding hydrochloric acid solution to the polyvinylformamide solution, heating, and performing hydrolysis reaction, adding glacial ethanol after the reaction, and drying the product to obtain a polyvinylamine hydrochloride solid; dissolving the polyvinylamine hydrochloride solid in deionized water, adding anion exchange resin to perform anion exchange, and vacuum filtering to obtain a polyvinylamine solution;

[0033] Preferably, the usage ratio of N-vinylformamide and 2,2-azobis(2-methylpropylimidamide) dihydrochloride is (10-40 g): (0.02-0.1 g);

[0034] And / or, the temperature of the free radical polymerization reaction is 50-70° C., and the time of the free radical polymerization reaction is 4-10 hours;

[0035] And / or, the temperature of the hydrolysis reaction is 60-80° C., and the time of the hydrolysis reaction is 2-5 h;

[0036] And / or, the concentration of the hydrochloric acid solution is 15-38 wt %, and the content of hydrochloric acid in the mixed solution of the polyvinyl formamide solution and the hydrochloric acid solution is 4-20 wt %.

[0037] The embodiments of the present invention also provide the use of the above-mentioned polyvinylamine gas separation membrane or the polyvinylamine gas separation membrane prepared by the above-mentioned preparation method in separating carbon dioxide from flue gas. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 is a SEM image of the silver nanowires prepared in step (1) of Example 1;

[0039] Figure 2 This is a SEM image of the silver nanowires with MOFs loaded on the surface obtained in step (2) of Example 1. DETAILED DESCRIPTION

[0040] Embodiments of the present invention are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to be used to explain the present invention, but should not be understood as limiting the present invention.

[0041] The polyvinylamine gas separation membrane of the embodiment of the present invention comprises polyvinylamine (PVAm) and silver nanowires with MOFs loaded on the surface (MOFs-AgNWs).

[0042] The polyvinylamine gas separation membrane of the embodiment of the present invention provides additional CO2 adsorption sites after MOFs are loaded on the surface of the silver nanowires, which is beneficial to improving the CO2 separation performance; the introduction of MOFs-AgNWs in the gas separation membrane can form intercalations between the primary amino groups of the polyvinylamine, avoiding the primary amino groups from forming crystalline regions through NH2-NH2 interactions and losing the function of transferring carbon dioxide; the introduction of MOFs-AgNWs in the gas separation membrane allows the silver nanowires to provide adsorption sites for CO2, play a role in physical adsorption, transfer CO2 to the other side of the membrane, and increase the transfer rate of CO2. The MOFs loaded on the surface of the silver nanowires can provide additional adsorption sites, further improving the CO2 separation performance.

[0043] In some embodiments, preferably, the content of the MOFs-AgNWs in the PVAm gas separation membrane is 20-85 wt %.

[0044] In the embodiment of the present invention, the dosage of MOFs-AgNWs is preferably selected. The addition amount within this range is conducive to the good dispersion effect of MOFs-AgNWs in polyvinylamine and is not easy to agglomerate, so that the prepared gas separation membrane has both high gas permeability and separation factor; if the dosage of MOFs-AgNWs is too high, the dispersibility of MOFs-AgNWs deteriorates and is easy to agglomerate, so that the interface compatibility between silver nanowires and polyvinylamine deteriorates, defects occur, and the separation factor of the polyvinylamine gas separation membrane becomes lower; if the dosage of MOFs-AgNWs is too low, the disruptive effect on the rearrangement of the polyvinylamine segments is reduced, and crystalline regions are easily generated, which leads to a lower gas permeability of the gas separation membrane.

[0045] In some embodiments, preferably, the diameter of the silver nanowire is 3 to 18 μm, and the length is 20 to 60 nm. It is understood that the diameter of the silver nanowire is an average diameter, such as 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, etc.; the length of the silver nanowire is an average length, such as 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, 55 nm, 60 nm, etc.

[0046] In the embodiment of the present invention, the size of the silver nanowires is optimized. The silver nanowires with a suitable aspect ratio can provide more MOFs loading sites, disperse better in polyvinylamine, and produce a better disturbance effect on the ordered rearrangement of the polyvinylamine chain segments. If the diameter of the silver nanowires is too large and the length is too long, the diameter will be larger after loading MOFs, and the dispersibility in polyvinylamine will deteriorate, and defects will be easily generated after film formation. If the diameter of the silver nanowires is too small and the length is too short, it cannot provide sufficient surface area for MOFs loading, and the disturbance effect on the ordered rearrangement of the polyvinylamine chain segments will deteriorate, which will slow down the permeation rate of the gas separation membrane.

[0047] In some embodiments, preferably, the loading amount of MOFs on the surface of the silver nanowires is 10-30 wt %.

[0048] In the embodiment of the present invention, the loading amount of MOFs on the surface of silver nanowires is preferably selected. The loading amount within this range can achieve MOFs coating on the surface of silver nanowires, provide additional CO2 adsorption sites, and the diameter of the silver nanowires is not too large, which is beneficial to improving the CO2 separation performance; if the loading amount of MOFs is too high, the MOFs coating layer on the surface of the silver nanowires is too thick, and too many uncoated MOFs particles are easily generated, making the size of the dopant uncontrollable and the regulation effect on the gas separation membrane worse; if the loading amount of MOFs is too low, it is not enough to coat the entire surface of the silver nanowires, and the CO2 adsorption sites are too few, which is not conducive to improving the CO2 separation performance.

[0049] In some embodiments, preferably, the thickness of the PVAm gas separation membrane is 300-800 nm. Further preferably, the viscosity-average molecular weight of the PVAm is 10000-50000 kDa, such as 10000 kDa, 15000 kDa, 20000 kDa, 25000 kDa, 30000 kDa, 35000 kDa, 40000 kDa, 45000 kDa, 50000 kDa, etc.

[0050] In the embodiment of the present invention, the molecular weight of PVAm is preferably selected. The molecular weight within this range can ensure that the prepared gas separation membrane has a higher separation coefficient and gas permeability; if the molecular weight of PVAm is smaller, the prepared gas separation membrane is prone to form defects, resulting in a lower separation coefficient; if the molecular weight of PVAm is larger, the prepared gas separation membrane is denser and the gas permeability rate is reduced.

[0051] The present invention also provides a method for preparing an ethyleneamine gas separation membrane, comprising the following steps:

[0052] (1) adding an organic ligand to a silver nanowire solution and performing ultrasonic dispersion treatment to obtain a mixed solution of the organic ligand and the silver nanowires;

[0053] (2) adding a metal salt solution to the mixed solution obtained in step (1), heating the mixed solution, stirring the mixed solution, and then standing the mixed solution for aging, washing and drying the obtained product to obtain MOFs-AgNWs, and using water as a solvent to obtain a MOFs-AgNWs solution;

[0054] (3) Add the MOFs-AgNWs solution obtained in step (2) into the polyvinylamine solution, and then add polyvinyl alcohol to obtain a slurry, and apply the slurry on the ultrafiltration membrane, followed by drying.

[0055] In some embodiments, preferably, in step (1), the organic ligand comprises at least one of 2,3,6,7,10,11-hexaaminotriphenyl hexahydrochloride, 1,3,5-benzenetricarboxylic acid, 1,3,5-tris(4-carboxyphenyl)benzene, 1,4-cyclohexanedicarboxylic acid or 1,10-phenanthroline;

[0056] and / or, the mass ratio of the organic ligand to the silver nanowire is 1:(2-10);

[0057] And / or, the preparation method of the silver nanowire solution comprises: adding polyvinyl pyrrolidone to ethylene glycol, heating it for reaction and then cooling it, adding silver nitrate solution and ferric chloride solution, cooling it after the silver nanowires are formed, centrifuging it with acetone to obtain a precipitate, and using ethanol as a solvent to prepare a silver nanowire solution.

[0058] Further preferably, the usage ratio of polyvinyl pyrrolidone to ethylene glycol is 4 to 20 g / L;

[0059] and / or, the concentration of the silver nitrate solution is 0.01-0.1 mol / L, the concentration of the ferric chloride solution is 0.1-1 mol / L, and the volume ratio of the ethylene glycol, the silver nitrate solution and the ferric chloride solution is (1-10):(1-5):1;

[0060] And / or, the reaction temperature is 140-180° C., and the reaction time is 0.5-2 h.

[0061] More preferably, the reaction is cooled to 20-30° C. after completion, and the silver nanowires are cooled to 20-30° C. after formation;

[0062] And / or, the centrifugal treatment time is 6 to 12 hours;

[0063] And / or, further comprising centrifugation washing the precipitate with ethanol, wherein the rotation speed of the centrifugation washing is 1000-5000 rpm, the centrifugation treatment is not less than 3 times, and the time of each centrifugation treatment is not less than 5 minutes;

[0064] And / or, the concentration of the silver nanowire solution is 1-10 wt %.

[0065] In some embodiments, preferably, in step (2), the metal salt solution comprises at least one of zinc nitrate, cobalt nitrate or copper nitrate;

[0066] and / or, the molar ratio of the metal to the organic ligand in the metal salt solution is 1:(2-12);

[0067] And / or, the stirring treatment temperature is 30-80°C, the stirring treatment time is 1-4 hours, and the static aging time is 0.5-12 hours;

[0068] And / or, the concentration of the silver nanowire solution with MOFs loaded on the surface is 1-10 wt %.

[0069] Further preferably, the concentration of the metal salt solution is 0.01-0.1 mol / L, and the metal salt solution is added to the mixed solution of the organic ligand and the silver nanowires at a speed of 1-3 s / drop;

[0070] And / or, the cleaning is performed by using acetone and deionized water in sequence, the drying temperature is 40 to 80° C., and the drying time is 10 to 14 hours;

[0071] And / or, the concentration of the MOFs-AgNWs solution is 1-10 wt %.

[0072] In some embodiments, preferably, in step (3), the MOFs-AgNWs account for 20 to 85% of the mass of the polyethyleneamine gas separation membrane;

[0073] And / or, the mass ratio of the polyvinyl amine to the polyvinyl alcohol is 20:(1-10);

[0074] And / or, the slurry is coated on the ultrafiltration membrane to a thickness of 50 to 200 μm;

[0075] And / or, the preparation method of the polyvinylamine solution comprises: dissolving N-vinylformamide and 2,2-azobis(2-methylpropylimidamide) dihydrochloride in deionized water, heating under nitrogen protection, and performing free radical polymerization reaction to obtain a polyvinylformamide solution; then adding hydrochloric acid solution to the polyvinylformamide solution, heating, and performing a hydrolysis reaction, adding glacial ethanol after the reaction, and drying the product to obtain a polyvinylamine hydrochloride solid; dissolving the polyvinylamine hydrochloride solid in deionized water, adding anion exchange resin to perform anion exchange, and vacuum filtering to obtain a polyvinylamine solution.

[0076] Further preferably, the usage ratio of N-vinylformamide and 2,2-azobis(2-methylpropylimidamide) dihydrochloride is (10-40 g): (0.02-0.1 g);

[0077] And / or, the temperature of the free radical polymerization reaction is 50-70° C., and the time of the free radical polymerization reaction is 4-10 hours;

[0078] And / or, the temperature of the hydrolysis reaction is 60-80° C., and the time of the hydrolysis reaction is 2-5 h;

[0079] And / or, the concentration of the hydrochloric acid solution is 15-38wt%, and the content of hydrochloric acid in the mixed solution of the polyvinyl formamide solution and the hydrochloric acid solution is 4-20wt%;

[0080] And / or, the anion exchange resin is a 717 type strong basic anion exchange resin;

[0081] and / or, performing ultrasonic treatment after adding polyvinyl alcohol, wherein the ultrasonic treatment time is 2 to 4 hours;

[0082] And / or, the drying process is carried out in a constant temperature and humidity chamber at a temperature of 30° C. and a relative humidity of 40%.

[0083] In some embodiments, preferably, the concentration of the polyvinyl formamide (PNVF) solution is 8-12wt%. Further preferably, the concentration of the polyvinyl formamide (PNVF) solution is 10wt%. In order to avoid the adverse effects of the instability of the concentration of the polyvinyl formamide (PNVF) solution on the reaction, the polyvinyl formamide (PNVF) solution is often dried first and then prepared into a solution with a concentration of 8-12wt% with deionized water.

[0084] The embodiments of the present invention also provide the use of the above-mentioned polyvinylamine gas separation membrane or the polyvinylamine gas separation membrane prepared by the above-mentioned preparation method in separating carbon dioxide from flue gas.

[0085] The technical solution of the present invention is described in detail below in conjunction with specific embodiments and drawings.

[0086] Example 1

[0087] (1) Preparation of silver nanowires (AgNWs): 25 mL of ethylene glycol (EG) was placed in a three-necked flask and preheated in an oil bath at 110°C for 0.5 h to remove the water therein. 0.25 g of polyvinyl pyrrolidone (PVP) was added to the EG, heated to 160°C, reacted for 1 h, and then cooled to 30°C. 10 mL of 0.1 mol / L AgNO3 solution and 8 mL of 0.5 mol / L FeCl3 solution were added. After the AgNWs were gradually formed, they were cooled to 30°C and centrifuged with acetone for at least 6 h until the precipitate and the supernatant were clearly separated. The precipitate was removed, washed with ethanol, and centrifuged at 5000 rpm for 3 times, each time for 5 min. After obtaining the AgNWs, ethanol was used as the solvent to prepare a silver nanowire solution with a content of 5 wt%.

[0088] (2) AgNWs with MOFs on the surface: Take 10 mL of the above silver nanowire solution, weigh 8 mg of 2,3,6,7,10,11-hexaaminotriphenylhexahydrochloride (HATP·6HCl) and 0.4 g of sodium acetate, put them into the AgNWs solution and perform ultrasound to fully dissolve them to obtain a HATP-AgNWs mixed solution. Then prepare a 0.05 mol / L Co(NO3)2 aqueous solution, take 10 mL of the Co(NO3)2 aqueous solution and add 10 mL of 25% ammonia water to obtain an alkaline Co(NO3)2 aqueous solution. Then, 3 mL of the alkaline Co(NO3)2 aqueous solution was slowly added to the HATP-AgNWs mixed solution at a rate of 2 s / drop, and stirred at 70°C for 2 h. After the reaction was completed, the product was washed with acetone and deionized water in turn, and finally placed in a drying oven at 70°C for 12 h to obtain a Co3(HITP)2-AgNWs composite material. Finally, a Co3(HITP)2-AgNWs solution with a content of 5 wt% was prepared using water as solvent.

[0089] (3) Preparation of polyvinylamine solution: 10g of deionized water was added to a three-necked flask, 40g of N-vinylformamide (NVF) was added under stirring, and then 0.057g of 2,2-azobis(2-methylpropylimidazole) dihydrochloride (AIBA) was added to completely dissolve it; then vacuum and fill with nitrogen, and the gas in the reaction system was replaced repeatedly for 3 times. Under nitrogen protection, the temperature was raised to 60°C, and a free radical polymerization reaction was carried out for 8 hours to obtain a polyvinylformamide (PNVF) solution. Subsequently, PNVF was vacuum dried at 30°C for 48h. The dried PNVF was prepared into a 10wt% solution, and then a certain amount of concentrated hydrochloric acid with a concentration of 30wt% was added through a separatory funnel, so that the content of hydrochloric acid in the mixed solution of polyvinylformamide solution and hydrochloric acid solution was 4wt%, and the temperature was raised to 70°C for hydrolysis reaction for 3h. After the temperature of the reaction system is lowered to room temperature, 400 mL of ice ethanol is added to obtain a white solid polyvinylamine hydrochloride precipitate, and the product is vacuum dried at room temperature for 24 hours to obtain a polyvinylamine hydrochloride solid product. The polyvinylamine hydrochloride solid product is dissolved in deionized water to prepare a 1.0 wt% solution, and then an excess of 717 type strong basic anion exchange resin is added to the solution for anion exchange, and finally vacuum filtration is performed to obtain a PVAm solution with a concentration of 1.0 wt%.

[0090] (4) Preparation of PVAm-MOFs / AgNWs separation membrane: 2 mL of the 5 wt% Co3(HITP)2-AgNWs solution prepared in step (2) was added to 20 mL of the PVAm solution prepared in step (3), stirred evenly and ultrasonicated for 2 h to obtain a PVAm-MOFs / AgNWs mixed solution. The front and back sides of the polysulfone PSf ultrafiltration membrane were washed with deionized water, and after the surface was dried, the above membrane was fixed on a flat glass panel. The distance between the scraper and the surface of the PSf membrane was adjusted to control the wet coating thickness to 200 μm, and the PVAm-MOFs / AgNWs solution was evenly scraped on the PSf ultrafiltration membrane to obtain a PVAm-MOFs / AgNWs wet film, which was placed in a constant temperature and humidity chamber for drying for 48 h (temperature of 30°C, relative humidity of 40%) to obtain a PVAm-MOFs / AgNWs separation membrane.

[0091] In the gas separation membrane prepared in this embodiment, the viscosity-average molecular weight of polyethylene amine is 18000 kDa, the content of AgNWs loaded with MOFs on the surface is 21 wt %, the average length of the silver nanowires is 13.4 μm, the average diameter of the silver nanowires is 35 nm, and the thickness of the gas separation membrane is 530 nm.

[0092] The silver nanowires prepared in this example were characterized by SEM. Figure 1 As shown, from Figure 1It can be seen that the prepared silver nanowires have very good size uniformity.

[0093] The surface-loaded silver nanowires of MOFs prepared in this example were characterized by SEM, and the results are shown in the attached figure. Figure 2 As shown, from Figure 2 It can be seen that MOFs are uniformly loaded on the surface of silver nanowires.

[0094] Example 2

[0095] The difference from Example 1 is that in step (4), 5 mL of 5 wt % Co3(HITP)2-AgNWs solution is added to 20 mL of PVAm solution.

[0096] Example 3

[0097] The difference from Example 1 is that in step (4), 8 mL of Co3(HITP)2-AgNWs was added to 20 mL of PVAm solution.

[0098] Example 4

[0099] The difference from Example 1 is that in step (4), 11 mL of Co3(HITP)2-AgNWs solution is added to 20 mL of PVAm solution.

[0100] Example 5

[0101] The difference from Example 1 is that in step (4), 15 mL of Co3(HITP)2-AgNWs solution is added to 20 mL of PVAm solution.

[0102] Example 6

[0103] The difference from Example 1 is that in step (4), 18 mL of Co3(HITP)2-AgNWs solution is added to 20 mL of PVAm solution.

[0104] Comparative Example 1

[0105] The difference from Example 1 is that step (2) is eliminated; in step (4), 2 mL of the 5 wt% AgNWs solution prepared in step (1) is added to 20 mL of the PVAm solution, and then the solution is scraped onto the PSf ultrafiltration membrane, the wet coating thickness is controlled to be 200 μm, and then the solution is placed in a constant temperature and humidity chamber and dried for 48 h.

[0106] Comparative Example 2

[0107] The difference from Example 1 is that steps (1) and (2) are eliminated; in step (4), the PVAm solution is directly scraped onto the PSf ultrafiltration membrane, the wet coating thickness is controlled to be 200 μm, and then placed in a constant temperature and humidity chamber for drying for 48 hours.

[0108] The performance of the gas separation membranes prepared in the above-mentioned Examples 1 to 6 and Comparative Examples 1 to 2 was tested using a separation membrane performance evaluation device (MGPT-I separation membrane performance evaluation device produced by Dalian Caribona Technology Co., Ltd.). The feed gas first enters the humidification tank to be humidified to saturated humidity, and then enters the membrane pool for testing. The feed gas is a CO2 / N2 mixed gas, the purge gas is helium, the pressure is 0.1MPa, and the permeate side pressure is normal pressure. The permeate side gas enters the gas chromatograph, and the obtained peak area is analyzed to obtain the separation coefficient, and the gas permeation rate is measured by an electronic soap film flowmeter. The test results are shown in Table 1.

[0109] Table 1

[0110]

[0111] As can be seen from Table 1, the higher the amount of MOFs-AgNWs added in Examples 1 to 6, the higher the CO2 permeation rate and the greater the CO2 / N2 separation coefficient. This is because the silver nanowires, which are dopants, are linear and can effectively disrupt the rearrangement of the PVAm segments, inhibit the formation of crystalline regions, and are beneficial to improving the N2 / CO2 separation performance. Examples 5-6 show that continuing to increase the amount of MOFs-AgNWs added will lead to a decrease in the CO2 / N2 separation coefficient. This is because after the doping amount is too much, the AgNWs dispersion deteriorates and is easy to agglomerate. The interface compatibility between the silver nanowires and PVAm deteriorates, and defects are easily generated at the interface, resulting in both CO2 and N2 passing through the membrane from the defects, increasing the gas permeation rate, but the CO2 / N2 separation effect deteriorates. The separation membrane must have both good CO2 permeation rate and CO2 / N2 separation coefficient, so Example 5 has the best separation effect, and the dispersion of the silver nanowires is the best at this time. Comparison 1 shows the effect of not modifying silver nanowires with MOFs. Compared with Example 1, it shows that MOFs can provide additional CO2 adsorption sites, which is beneficial to improve the CO2 separation performance. Comparative Example 2 is a pure PVAm membrane without adding silver nanowires. Its CO2 / N2 separation coefficient is high, but the CO2 permeation rate is poor, indicating that at this time, due to the hydrogen bonding of NH2-NH2 in the PVAm segment, the PVAm tends to be regularly rearranged, forming a poor crystalline region structure, resulting in a low CO2 permeation rate.

[0112] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0113] Although the above embodiments have been shown and described, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. Changes, modifications, substitutions and variations of the above embodiments by those of ordinary skill in the art are all within the scope of protection of the present invention.

Claims

1. A polyethyleneamine gas separation membrane, characterized in that Includes polyvinylamine and silver nanowires with MOFs loaded on the surface.

2. The polyethyleneamine gas separation membrane according to claim 1, characterized in that The content of the silver nanowires loaded with MOFs on the surface in the polyethylene amine gas separation membrane is 20 to 85 wt %.

3. The polyethyleneamine gas separation membrane according to claim 1, characterized in that The diameter of the silver nanowire is 3-18 μm, and the length is 20-60 nm.

4. The polyethyleneamine gas separation membrane according to claim 1, characterized in that The loading amount of MOFs on the surface of the silver nanowire is 10-30 wt %.

5. The polyethyleneamine gas separation membrane according to claim 1, characterized in that The thickness of the polyvinylamine gas separation membrane is 300-800 nm.

6. The method for preparing a polyethyleneamine gas separation membrane according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) adding an organic ligand to a silver nanowire solution and performing ultrasonic dispersion treatment to obtain a mixed solution of the organic ligand and the silver nanowires; (2) adding a metal salt solution to the mixed solution obtained in step (1), heating the mixed solution, stirring the mixed solution, and then standing the mixed solution for aging, washing and drying the obtained product to obtain silver nanowires with MOFs on the surface, and using water as a solvent to obtain a silver nanowire solution with MOFs on the surface; (3) adding the surface-loaded MOFs silver nanowire solution obtained in step (2) to the polyvinylamine solution, and then adding polyvinyl alcohol to obtain a slurry, and coating the slurry on an ultrafiltration membrane, followed by drying.

7. The method for preparing a polyethyleneamine gas separation membrane according to claim 6, characterized in that: In the step (1), the organic ligand includes at least one of 2,3,6,7,10,11-hexaaminotriphenyl hexahydrochloride, 1,3,5-benzenetricarboxylic acid, 1,3,5-tri(4-carboxyphenyl)benzene, 1,4-cyclohexanedicarboxylic acid or 1,10-phenanthroline; and / or, the mass ratio of the organic ligand to the silver nanowire is 1:(2-10); And / or, the preparation method of the silver nanowire solution comprises: adding polyvinyl pyrrolidone to ethylene glycol, heating it for reaction and then cooling it, adding silver nitrate solution and ferric chloride solution, cooling it after the silver nanowires are formed, centrifuging it with acetone to obtain a precipitate, and preparing the silver nanowire solution with ethanol as solvent; Preferably, the dosage ratio of polyvinyl pyrrolidone and ethylene glycol is 4-20 g / L; and / or, the concentration of the silver nitrate solution is 0.01-0.1 mol / L, the concentration of the ferric chloride solution is 0.1-1 mol / L, and the volume ratio of the ethylene glycol, the silver nitrate solution and the ferric chloride solution is (1-10):(1-5):1; and / or, the reaction temperature is 140-180° C., and the reaction time is 0.5-2 h.

8. The method for preparing a polyethyleneamine gas separation membrane according to claim 6, characterized in that: In the step (2), the metal salt solution includes at least one of zinc nitrate, cobalt nitrate or copper nitrate; and / or, the molar ratio of the metal to the organic ligand in the metal salt solution is 1:(2-12); And / or, the stirring treatment temperature is 30-80°C, the stirring treatment time is 1-4 hours, and the static aging time is 0.5-12 hours; And / or, the concentration of the silver nanowire solution with MOFs loaded on the surface is 1-10 wt %.

9. The method for preparing a polyethyleneamine gas separation membrane according to claim 6, characterized in that: In the step (3), the silver nanowires loaded with MOFs on the surface account for 20 to 85% of the mass of the polyethylene amine gas separation membrane; And / or, the mass ratio of the polyvinyl amine to the polyvinyl alcohol is 20:(1-10); And / or, the slurry is coated on the ultrafiltration membrane to a thickness of 50 to 200 μm; And / or, the preparation method of the polyvinylamine solution comprises: dissolving N-vinylformamide and 2,2-azobis(2-methylpropylimidamide) dihydrochloride in deionized water, heating under nitrogen protection, and performing free radical polymerization reaction to obtain a polyvinylformamide solution; then adding a hydrochloric acid solution to the polyvinylformamide solution, heating, and performing a hydrolysis reaction, adding glacial ethanol after the reaction, and drying the product to obtain a polyvinylamine hydrochloride solid; dissolving the polyvinylamine hydrochloride solid in deionized water, adding anion exchange resin, performing anion exchange, and vacuum filtering to obtain polyvinylamine solution; preferably, the dosage ratio of the N-vinylformamide and 2,2-azobis(2-methylpropylimidamide) dihydrochloride is (10-40g):(0.02-0.1g); and / or, the temperature of the free radical polymerization reaction is 50-70°C, and the time of the free radical polymerization reaction is 4-10h; and / or, the temperature of the hydrolysis reaction is 60-80°C, and the time of the hydrolysis reaction is 2-5h; and / or, the concentration of the hydrochloric acid solution is 15-38wt%, and the content of hydrochloric acid in the mixed solution of the polyvinylformamide solution and the hydrochloric acid solution is 4-20wt%.

10. Use of the polyvinylamine gas separation membrane according to any one of claims 1 to 5 or the polyvinylamine gas separation membrane prepared by the preparation method according to any one of claims 6 to 9 in separating carbon dioxide from flue gas.

Citation Information

Patent Citations

  • MOFs based carbon dioxide adsorbent, preparation method and application thereof

    CN104056598A

  • Novel high-efficiency haze filtration silver nanowire net and MOFs composite porous fiber film material and preparation method thereof

    CN110075815A

  • Ag-MOF composite chitosan-based film as well as preparation method and application thereof

    CN114634657A

  • Separation membrane, preparation method of separation membrane and filtering device using separation membrane

    CN117123061A

  • Composite antibacterial filtering fiber membrane for visually detecting sulfur-containing compounds

    CN117166136A